Participation du public dans la gouvernance de l’environnement et du territoire : pour améliorer l’instrumentation - Carlo Prévil (VertigO, 2009)
Public participation is a key issue in planning and habitat design according to sustainable development paradigm. Beyond sociopolitical demands and legal references, the challenge is to adapt planners’ practices to this global emerging issue related to governance. In some situations, it should lead to deep and structural changes in territorial decisional process. In this paper, we analyze how instrumental dimension of public participation can induce transformation, even re-engineering, of planning practices in a clear perspective to territorial and environmental governance. Finally, we propose an integrated decisional process approach so called OSCAR (observation, spatialization, comprehension, action and retroaction). This exploratory approach could constitute a kind of contribution for new know-how (savoir-faire) for intimate integration of: information, participation and governance principles in renewed practices for planners and environmentalists.